The effect of Sn on autoclave corrosion performance and corrosion mechanisms in Zr-Sn-Nb alloys - Wei, J; Frankel, P; Polatidis, E; Blat, M; Ambard, A; Comstock, R; Hallstadius, L; Hudson, D; Smith, G; Grovenor, C; Klaus, M; Cottis, R; et al. (2013)
The desire to improve the corrosion resistance of Zr cladding material for hig h burn-up has resulted in a general trend among fuel manufacturers to develop alloys with reduced levels of Sn. While commonly accepted, the reason for the improved corrosion performance observed for low-tin zirconium alloys in high-temperature aqueous environments remains unclear. High-energy synchrotron X-ray diffraction was used to characterize the oxides formed by autoclave exposure on Zr-Sn-Nb alloys with tin concentration ranging from 0.01 to 0.92 wt.%. The alloys studied included the commercial alloy ZIRLO® (ZIRLO® is a registered trademark of Westinghouse Electric Company LLC in the USA and may be registered in other countries throughout the world. All rights reserved. Unauthorized use is strictly prohibited.) and two variants of ZIRLO with significantly lower tin levels, referred to here as A-0.6Sn and A-0.0Sn. The nature of the oxide grown on tube samples from each alloy was investigated via cross-sectional scanning electron microscopy. Atom probe analysis of ZIRLO demonstrated that the tin present in the alloy passes into the oxide as it forms, with no significant difference in the Sn/Zr ratio between the two. Synchrotron X-ray diffraction measurements on the oxides formed on each alloy revealed that the monoclinic and tetragonal oxide phases display highly compressive in-plane residual stresses with the magnitudes dependent on the phase and alloy. The amount of tetragonal phase present and, more importantly, the level of tetragonal-to-monoclinic phase transformation both decrease with decreasing tin levels, suggesting that tin is a tetragonal oxide phase stabilizing element. It is proposed that in Zr-Nb-Sn alloys with low Sn, the tetragonal phase is mainly stabilized by very small grain size and therefore remains stable throughout the corrosion process. In contrast, alloys with higher tin levels can in addition grow larger, stress stabilized, tetragonal grains that become unstable as the corrosion front continues to grow further inwards and stresses in the existing oxide relax. © 2013 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.